2015
DOI: 10.5152/ejp.2015.83803
|View full text |Cite
|
Sign up to set email alerts
|

Dyspnea Associated with Silicone Breast Implant Rupture

Abstract: We present a case of a 48-year-old woman with a significant history of atopy. She presented with a 1-month history of dyspnea on exertion. Pulmonary function testing was normal, with no obstruction or reversibility post-bronchodilation. Bilateral breast implant rupture was detected on further investigation for a left upper lobe nodule, and the patient underwent bilateral implant removal. There was an improvement in her respiratory symptoms. Systemic symptoms, labeled as "Autoimmune/Inflammatory Syndrome Induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…[ 1 2 3 ] There have been case reports on patients with silicone breast implants presenting with type IV delayed hypersensitivity reaction. [ 14 ] Histologically, there is chronic inflammation showing granulation tissue and foreign-body reaction[ 15 ] which in this case, has been revealed on biopsy of the lymph node, subcutaneous, and intramuscular deposits.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 3 ] There have been case reports on patients with silicone breast implants presenting with type IV delayed hypersensitivity reaction. [ 14 ] Histologically, there is chronic inflammation showing granulation tissue and foreign-body reaction[ 15 ] which in this case, has been revealed on biopsy of the lymph node, subcutaneous, and intramuscular deposits.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39][40] A case series and one case study identified symptoms of platinum salt hypersensitivity in silicone breast implant recipients, and attributed the symptoms to platinum present in the silicone breast implants. 41,42 However, this case series was criticized due to a lack of providing causal evidence supporting their conclusion. 43 Recently, a company in the Netherlands, named Hair Diagnostix, started offering a commercial platinum hair screening test to women with silicone gel-filled breast implants.…”
Section: Introductionmentioning
confidence: 98%
“…36–40 A case series and one case study identified symptoms of platinum salt hypersensitivity in silicone breast implant recipients, and attributed the symptoms to platinum present in the silicone breast implants. 41,42 However, this case series was criticized due to a lack of providing causal evidence supporting their conclusion. 43…”
Section: Introductionmentioning
confidence: 98%